2015
DOI: 10.1371/journal.pone.0124648
|View full text |Cite
|
Sign up to set email alerts
|

Response to Vitamin B12 and Folic Acid in Myalgic Encephalomyelitis and Fibromyalgia

Abstract: BackgroundPatients with myalgic encephalomyelitis (ME, also called chronic fatigue syndrome) may respond most favorably to frequent vitamin B12 injections, in vital combination with oral folic acid. However, there is no established algorithm for individualized optimal dosages, and rate of improvement may differ considerably between responders.ObjectiveTo evaluate clinical data from patients with ME, with or without fibromyalgia, who had been on B12 injections at least once a week for six months and up to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…The results were at the time interpreted as suggesting a block of inflow over the blood brain barrier of B12 and/or folic acid ( 277 ). The derangement in one-carbon metabolism is supported by 20 years’ experience of vitamin B12 and B9 treatment in ME/CFS patients, which tends to diminish impaired cognition (“brain fog”) ( 306 ). It is not immediately evident why the one-carbon metabolic pathway would change after a block of aerobic energy production.…”
Section: Can Autoimmunity Explain Energy Metabolic Disturbances and Pmentioning
confidence: 99%
“…The results were at the time interpreted as suggesting a block of inflow over the blood brain barrier of B12 and/or folic acid ( 277 ). The derangement in one-carbon metabolism is supported by 20 years’ experience of vitamin B12 and B9 treatment in ME/CFS patients, which tends to diminish impaired cognition (“brain fog”) ( 306 ). It is not immediately evident why the one-carbon metabolic pathway would change after a block of aerobic energy production.…”
Section: Can Autoimmunity Explain Energy Metabolic Disturbances and Pmentioning
confidence: 99%
“…However, further research is needed because the studies carried out to date have been small and have used inconsistent dosing regimens and/or non‐biologically active forms of vitamin B 12 (hydroxocobalamin) (Swanink et al, ; Bjorkegren, ; Norberg, ; Hagglof, ). Recently, this question has been addressed (Regland et al, ), drawing on 15 years' experience of treating CFS/ME patients with vitamin B 12 (methylcobalamin, as the biologically active form). During this time, the CFS/ME patients were shown to respond best to the injected form of vitamin B 12 .…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…This research group concluded (Regland et al, ) that frequent injections of highly concentrated methylcobalamin combined with an individual daily high dose of oral folic acid may be safe and effective for fatigue and other CFS/ME symptoms. Moreover, CFS/ME patients should be tested for certain opioid and analgesic drugs and for co‐existing thyroid dysfunction.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…But we have asked ourselves the question of whether it is a direct complication of the disease or is it a co-morbidity. However, Regland B. et al [10] showed that the injection of vitamin B12 leads to an improvement in myalgic encephalomyelitis syndrome.…”
Section: Discussionmentioning
confidence: 99%